Study of morphological and biochemical blood composition in rats on the background of quercetin loading - V. V. Leonov; A. A. Novosyolov; D. A. Chicherina; E. Y. Shestitko; O. N. Pavlova; O. N. Gulenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
The interaction of warm-blooded organisms with the environment is always reflected in the homeostatic equilibrium of metabolic processes. The dynamics of redox processes occurring in the body is primarily reflected in hematological indices. The aim of the investigation was to study reactive changes of morphological and biochemical blood composition in rats against the background of quercetin load. Objectives: to analyze the dynamics of morphological and biochemical composition of animal blood at the background of intragastric loading with quercetin in the form of oil solution during 30 days. The study was performed on 80 white mongrel male rats weighing 190-210 g, which were divided equally into control (intact) and experimental groups. The study of reactive changes in the morphological and biochemical composition of the blood of rats under the influence of quercetin was conducted in the dynamics before the experiment, as well as on 1, 3, 5, 7, 10, 15, 20, 25 and 30 days of experiment. It was found that against the background of additional loading with oil solution of quercetin in rats there were reactive changes in the morphological composition of the blood, which are reflected in the increased number of red blood cells, concentration of hemoglobin and leucocytes within the physiological norm, as well as changes in the biochemical composition of the blood, expressed in increased concentration of albumin and decreased concentration of albumin fractions in the rats of the experimental group compared with intact animals.